Diseño de puente desplazable para la presa sobre el río Cariblanco del Centro de Generación Toro - Arias-Porras, María Fernanda (Instituto Tecnológico de Costa Rica, 2014)
The project consists of the structural design of a movable steel truss bridge that will be built over a small dam in the water intake of the Cariblanco River, located in Sarapiquí, Alajuela. This is part of the Cariblanco Hydroelectric Project, owned by Instituto Costarricense de Electricidad. The dimensions of the bridge are variable. The longest side is 16,50m long, while the shortest is 9,00m long. As a special characteristic, the bridge must have the possibility of moving alongside the dam without obstructing it. The first step of the design process is the modelling of the frame using structural analysis software (SAP2000). Then the design of each single component of the structure, according to AASHTO 2005 code for bridge design, using LRFD methodology and taking into consideration the regulations stated in March 2013 by Colegio Federado de Ingenieros y de Arquitectos de Costa Rica. Since the bridge will not be subject to large load cycles, some revisions of weight limits were omitted. This made possible to obtain a lighter structure to facilitate its movement.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: LRFD; AASHTO; Código Sísmico de Costa Rica-2010; Puente tipo armadura; Cercha acero